2009
DOI: 10.1007/s00709-008-0029-0
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and function of epistomatal mucilage plugs

Abstract: Investigation of 67 gymnosperm and angiosperm species belonging to 25 orders shows that epistomatal mucilage plugs are a widespread phenomenon. Measurements of the leaf water status by using the leaf patch clamp pressure technique suggest that the mucilage plugs are involved in moisture uptake and buffering leaf cells against complete turgor pressure loss at low humidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 12 publications
0
21
0
Order By: Relevance
“…(2007) for several tall tree species. A related study, including gymnosperms, revealed that three species of Araucaria ( A. bidwillii , A. robusta and A. cunnighamii ) have numerous epistomatal mucilage plugs (Westhoff et al. 2009).…”
Section: Introductionmentioning
confidence: 99%
“…(2007) for several tall tree species. A related study, including gymnosperms, revealed that three species of Araucaria ( A. bidwillii , A. robusta and A. cunnighamii ) have numerous epistomatal mucilage plugs (Westhoff et al. 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Arabidopsis thaliana) are investigated. It also leads to erroneous results if the xylem vessels contain gel-like compounds (mucopolysaccharides) and/or the leaves contain mucilage containing epistomatal plugs by which water loss and moisture uptake from the atmosphere is regulated (Zimmermann et al 2004, 2007, Westhoff et al 2009b. Excessive overpressures are needed to squeeze out water from mucilage-containing leafy twigs.…”
Section: Magnetic Probe Versus Pressure Chamber Measurementsmentioning
confidence: 99%
“…Electric potential changes have also been detected recently between the base of the stem and upper leaf of avocado trees (Persea americana) in response to drought, irrigation and diurnal light/dark regimes (Fromm 2006, Davies 2006, Gurovich and Hermosilla 2009). Gurovich and others discuss propagation of the electric signals through the tree, but ignore that pressure propagation through the xylem vessels and tissue is most likely the primary event that leads subsequently to electrical changes on the cellular level (see also Westhoff et al 2008Westhoff et al , 2009b. No doubt, concomitant probe and electrical potential measurements will contribute to the elucidation of signals causing stomata closure, i.e., primary hydraulic event and the secondary electrical responses.…”
Section: Effects Of Stomata Aperture Oscillations On Turgor Pressurementioning
confidence: 99%
“…The ZIM system has been tested in a variety of forest tree species [165], grapevines [166,167], and grapefruit [167], banana [168], persimmon [169] and olive trees [49,[170][171][172], as well as in herbaceous crops such as tomato [173], canola [174] and wheat [175,176]. Also, comparative studies of the ZIM system vs. Scholander-type chambers have been made by Westhoff et al [166] for grapevines, by Rüger et al [165] for eucalyptus, avocado, grapefruit, beech and oak, and by Ben-Gal et al [170] and Fernández et al [49] for olive. These studies showed that the ZIM system is robust, relatively inexpensive, and suitable for automatic and continuous recording under field conditions for long periods of time, and that it has a great potential as a water stress indicator in vineyards and fruit tree orchards.…”
Section: Leaf Turgor Pressurementioning
confidence: 99%